Multiferróicos monofásicos a base de Pb(Fe2/3W1/3)O3-PbTiO3: acoplamento magnetoelétrico intrínseco - Fraygola, Bárbara Maraston (Universidade Federal de São Carlos, 2010)
Multiferroic ceramic solid solutions between the ferroelectric relaxor Pb(Fe2/3W1/3)O3 (PFW) and normal ferroelectric PbTiO3 (PT) [PFW-PT] has been synthesized by a modified B-site precursor method and characterized by X-ray diffraction, differential thermal analysis, dielectric, electric, magnetic and anelastic measurements. A two-stage solid-state reaction turned out to be appropriate for the formation of the majoritary PFW phase as well as PFW-PT solid solutions, with low percentage of spurious phases, high densities, dielectric constant and electric resistivities. Intrinsic relationship between structure, composition, magnetic ordering and dielectric proprieties was discussed. Dielectric properties have been tailored by adding PbTiO3, bringing the ferroelectric transition toward the room temperature, transforming the phase transition from diffuse, typical for ferroelectric relaxors, to a sharp one, characteristic of normal ferroelectrics. Two types of superexchange magnetic interactions and a succession of magnetic transitions with Neel temperatures dependent on the composition were found in the solid solutions. The magnetic ordering at TN1 is expected to vanish with PT addition, for higher amounts of PT to 30 percent. For 12-13%PT, the samples are multiferroic (presenting ferroelectric and antiferromagnetic ordering) below 237K. Anomalies in the temperature dependence of the elastic constants have been observed at TN and TC for all samples, indicating that the magnetoelectric coupling between the ferroelectric and antiferromagnetic orders occurs via strain . The value of the magnetoelectric coefficients η were estimated for all samples, from the measured values of their magnetic susceptibility, dielectric constant, magnetoelastic and electroelastic coefficients. Additionally, an interplay between ferroelectric and ferromagnetic properties of the samples, as well as the influence of the proximity of the temperatures of the establishment of both orderings with intrinsic magnetoelectric coupling coefficient was established.
Keywords: Física da matéria condensada; Cerâmicas multiferróicas; Magnetoelétricos; Ferroelétricos; Ultra-som; CIENCIAS EXATAS E DA TERRA::FISICA::FISICA DA MATERIA CONDENSADA